Crescimento, propriedades estruturais e eletrônicas de grafeno epitaxial - Além Mar Bernardes Gonçalves (2012)
This thesis presents studies on the structural properties of multilayeredfilms of epitaxial Graphene grown on silicon carbide (on both polar faces of the substrate). In the first study we have identified the existence of a metastable phase which occurs during the growth of multilayer epitaxial Graphene on the silicon face of SiC. This phase is composed of carbon and silicon atoms that have not completely sublimated and that bond to Graphene forming a different material. The experimental verification was obtained by X-ray diffraction and scanning tunneling microscopy. Theoretical calculations were used to confirm the stability of the structure. In the second study, multilayer epitaxial Graphene was produced on the carbon face SiC at atmospheric pressure. A study, by Xray diffraction and Raman spectroscopy, was performed on a set of samples as a function of growth time and showed that the Graphene layers grow decoupledand with rotational disorder. It is also present in this thesis the results obtained during my stay at Rutgers University, where I performed the growth of Graphene by chemical vapour deposition on metal surfaces. I also built a device capable of performing the transfer of monolayers of Graphene on crystals of Boron nitride, allowing the production of high mobility Graphene devices.